PEMBENTUKAN BISNIS YANG BERETIKA MELALUI EDUKASI ETIKA BISNIS UNTUK PENGUSAHA UMKM WARUNG MAKAN NASI GORENG - Sapitri, Winda; Aristha, Diandra Sofia; Saputra, Agam Aditya; Hudzaiva, Afta; Hasanah, Hijjatul (CV Sentra Nusa Connection, 2024)
This article presents the results of observations of micro, small and medium enterprises (MSMEs) in the form of fried rice food stalls. Through direct observation, it was discovered that the shop did not understand business ethics, but after being educated about business ethics, they implemented creative marketing strategies, such as using social media to increase visibility. Apart from that, aspects of cleanliness, service and menu variations are important factors in attracting customers. This educational observation provides in-depth insight into the factors that influence the success of MSMEs in the culinary industry. This activity was carried out using the Asset Based Communities Development (ABCD) approach. The implications of this activity can help direct efforts to develop sustainable and ethical MSMEs in the Fried Rice industry and other business sectors.